PENGARUH PEMAHAMAN AJARAN TRI NGA DAN RELIGIUSITAS TERHADAP NIAT PATUH CALON WAJIB PAJAK - Wardani, Dewi Kusuma; Rohmayanti, Tri (Jurnal Manajemen Terapan dan Keuangan, 2024)
This research aims to test whether understanding of tri nga teachings and religiosity have an influence on prospective taxpayers' intention to comply. This research uses a quantitative approach using primary data. The population in this study were students in Indonesia and the sample obtained was 200 respondents. The method used in determining the sample is the snowball sampling method. Data collection was carried out using a questionnaire distributed online via Google Form. This research data was analyzed using a data processing application, namely using the SPSS version 23 application. The results of this study show that the variable understanding the teachings of the tri nga (X1) has a positive effect on the taxpayer's intention to comply, while the religiosity variable (X2) has no effect on the candidate's intention to comply. taxpayer(Y).